2008
DOI: 10.1111/j.1349-7006.2008.00875.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of lung adenocarcinoma in transgenic mice expressing activated EGFR driven by the SP‐C promoter

Abstract: To investigate the role of an activating epidermal growth factor receptor (EGFR) mutation in lung cancer, we generated transgenic mice expressing the delE748-A752 mutant version of mouse EGFR driven by the SP-C promoter, which is equivalent to the delE746-A750 mutation found in lung cancer patients. Strikingly, the mice invariably developed multifocal lung adenocarcinomas of varying sizes at between 5 and 6 weeks of age, and they died from tumor progression approximately 2 months later if left untreated. Daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 40 publications
(50 reference statements)
1
25
0
Order By: Relevance
“…2A). We previously reported that no interstitial lung disease was found in the mice treated with gefitinib (29) and no other toxicities of skin, intestine, and liver developed in this study (Supplementary Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2A). We previously reported that no interstitial lung disease was found in the mice treated with gefitinib (29) and no other toxicities of skin, intestine, and liver developed in this study (Supplementary Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…The transgenic mice had no distant metastases (29,30). All animals were kept under pathogen-free conditions with abundant food and water as specified in the guidelines of the Department of Animal Resources, Okayama University Advanced Science Research Center, Okayama, Japan.…”
Section: Animal Husbandry and Drug Treatmentmentioning
confidence: 99%
“…21 However, Ohashi et al reported that transgenic mice expressing the delE748-A752 mutant version of mouse EGFR driven by the SP-C promoter developed multifocal lung adenocarcinomas with the AAH and BAC (lepidic) pattern at 3-5 weeks of age. 25 Others also concluded that the mutations are early, pre-invasive changes, whereas copy number gains are later events associated with the invasive phenotype. 23,24 In the present study, the micro-dissected BAC (lepidic) pattern was thought to correspond to a pre-invasive tumor lesion: EGFR mutations were more common, though not significantly, in the BAC (lepidic) pattern.…”
Section: Discussionmentioning
confidence: 99%
“…We generated transgenic mice expressing the delE748-A752 mutant of mouse Egfr, which is equivalent to the delE746-A750 mutant (10). The transgenic mice used the SP-C promoter to express mutated Egfr in type II alveolar cells.…”
Section: Transgenic Mouse Modelmentioning
confidence: 99%
“…We established transgenic mice expressing the delE748-A752 mutant of mouse Egfr, which corresponded to the delE746-A750 mutant of human EGFR (10). In the transgenic mice, pSTAT3 was overexpressed in the bronchioloalveolar carcinoma component around the adenocarcinoma center (11).…”
Section: Introductionmentioning
confidence: 99%